Fatigue modifies hip and knee kinematics during single- and double-leg dynamic tasks: An investigation with female handball players - Bedo, B. L.; Catelli, D. S.; Lamontagne, M.; Moraes, R.; Pereira, D. R.; Graça, J. B.; Santiago, P. R. P. (Journal of Sports Sciences, 2022)
This study investigated the effect of a handball-specific fatigue protocol on hip and knee kinematics. Twenty female handball athletes performed three trials of the single-leg landing (SLL), sidestep cutting manoeuvre (SCM), and drop vertical jump (DVJ) before and after the fatigue protocol. Knee and hip angle waveforms were compared using statistical parametric mapping (p < 0.05). During the SLL, the fatigue increased hip adduction (4-7% cycle) and knee abduction (4-9% and 25-27%). For the SCM, hip flexion was reduced under fatigue during 14-29% and 44-68% of the cycle. Similarly, the knee flexion decreased between 7-36% and 53-73%. Besides, during the fatigue state, the athletes reduced the hip abduction between 0-11% of the cycle and increased the knee abduction between 20-23%. During the DVJ task, when fatigued, the hip flexion decreased between 19-44% of the cycle and the knee flexion between 1-16% and 18-77%. The fatigue protocol altered the lower limb kinematics, decreasing knee and hip flexions during the SCM and DVJ and increasing the knee valgus during both single-leg landing tasks.